Problemy środowiskowe polskiej polityki przestrzennej w perspektywie kreowania jednolitej przestrzeni europejskiej - Przybyła, Zbigniew; Potocki, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The Polish space as a part of the European territory requires to interprete on the level of a spatial policy in a context of the Polish accession to the European Union. The paper presents the most important environmental problems of Polish spatial management (due to "Conception of Policy of Spatial Management of the Countr”) on a background of historical and contemporary aspects of European policy. The example of the govemmental project of Polish network of protected areas "Nature 2000" shows that there are serious problems of integration of Polish spatial policy into the European Union’s policy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 86-96